A Pilot Study on Standardized In-hospital Education About Heart Failure Conducted During the First Days After Decompensation. Issue 1 (30th December 2022) - Siennicka, Agnieszka; Biegus, Jan; Gajewski, Piotr; Młynarska, Katarzyna; Sokolski, Mateusz; Siwołowski, Paweł; Zymliński, Robert; Jedynak, Kamila; Ponikowska, Beata; Urban, Szymon
Abstract : Introduction: Education addressed to heart failure (HF) patients constitutes an important element of modern comprehensive treatment programs. The present article demonstrates a novel method of standardized in-hospital education addressed to patients admitted due to decompensation in HF. Methods: This pilot study was conducted among 20 patients [19 men, age 63 ± 16 years, NYHA (Classification according to New York Heart Association) on admission (II/III/IV): 5/25/70%]. Five-day education was based on individual sessions conducted using colorful boards demonstrating selected, highly practical elements of the knowledge about HF management, prepared by experts in HF management (medical doctors, a psychologist, and a dietician). The level of knowledge about HF was measured before and after education, based on a questionnaire prepared by the authors of the boards. Results: All patients experienced an improvement of their clinical status (confirmed by reduced New York Heart Association class and body mass, both P < 0.05). Mini Mental State Exam (MMSE) confirmed that no one demonstrated cognitive impairment. The score reflecting the level of knowledge about HF improved significantly after 5 days of in-hospital treatment accompanied by education ( P = 0.0001). Conclusions: We showed that the proposed model of education addressed to patients with decompensated HF, conducted using colorful boards demonstrating selected, highly practical elements of the knowledge about HF management, prepared by experts in HF management lead to significant increase of HF-related knowledge.